KONSEP JAHALAT AL-RUWAH DAN PENINGKATANNYA DALAM HADISPERSPEKTIF MUHAMMAD ‘AJJAJ AL-KHATIB DAN MAHMUD AL-TAHHAN - Habieb Bullah (Diroyah : Jurnal Studi Ilmu Hadis, 2019)
In the development of the scientific tradition of hadith is always interesting to discuss. This development was not missed by contemporary era hadith scholars. their participation to contribute scientific scholarship in the future. Surely the struggle was only aimed at maintaining the authenticity of the Prophet's hadith from counterfeiting. Among these contemporary scholars are Muhammad ‘Ajjaj al-Khatib and Mahmud al-Tahhan. They have different concepts about the problem in testing the personal qualities of the narrator. One of the objects studied is related to the concept of the hidden narrator (jahalat al-ruwah) and improving the quality of his hadith. Basically a hadith that is detected by the hidden narrators, the quality of the hadith becomes daif (weak). According to Muhammad ‘Ajjaj al-Khatib, every hadith whose daif is caused by the hiding of the narrator or the personal quality of the narrator is unknown, the tradition cannot be elevated from daif to hasan lighairihi even though it is supported by many sanad. This is due to the very bad cause of the daif. Unlike the case according to Mahmud al-Tahhan, daif hadith can be lifted from the quality of daif to hasan lighairihi, even though the cause of his daif is the hiding of the narrator (jahalat al-ruwah). The statements of the two scholars indicate there are differences in understanding of the concept of Jahalat al-Ruwah and its improvement. This study uses a descriptive analysis method in which it contains an analysis of the concept of Jahalat al-Ruwah and its improvement in the hadith perspective of Muhammad 'Ajjaj al-Khatib and Mahmud al-Tahhan. This research produced a critical view of Muhammad' Ajjaj al-Khatib and Mahmud al- Tahhan is related to the personal qualities of the hadith narrators.